CircRNA-mediated heterogeneous ceRNA regulation mechanism in periodontitis and peri-implantitis - Hailun Zhou; Rong Xiang; Wenjin Chen; Yuanyuan Peng; Zhiyong Chen; Wenxia Chen; Li Tang (European Journal of Medical Research)
Abstract Background Performing a comprehensive study on the differential expression of mRNAs, miRNAs, and circRNAs in the context of peri-implantitis and periodontitis has beneficial advantages to identify unique molecular signatures and pathways that may contribute to our understanding of these conditions. Methods Gingival tissues from healthy individuals and peri-implantitis and periodontitis patients were obtained to identify differential expression genes (DEG) by Illumina HiSeq 2500 instrument. Differential expression analysis was conducted using R statistical software, with significance set at P < 0.05 and fold greater than 2. Functional enrichment analysis of the DEGs was conducted using the Reactome, Gene ontology and KEGG databases. Results Significant differences in mRNA, miRNA, and circRNA profiles were identified between healthy gingival tissues. The top DEGs comprising 6 circRNAs, 2 miRNAs, and 4 mRNAs were identified and the constructed ceRNA network, elucidates their involvement in key signaling pathways such as ErbB, Wnt, and mTOR, which are crucial for understanding the inflammatory progression of these conditions. Conclusions This study highlights a heterogeneous circRNA-mediated ceRNA regulatory mechanism in peri-implantitis and periodontitis, activating signaling pathways and regulating gene expression. Key findings including a detailed analysis of the transcriptional landscape and identification of unique molecular signatures, pathways and cellular components in gingival tissues, offering insights into the molecular differences between peri-implantitis and periodontitis. The study may contribute to the understanding of the pathological mechanisms of these diseases and may aid in the development of targeted therapies.